ANALISIS PERAN PETANI DALAM KONSERVASI LAHAN PERTANIAN BERBASIS KEARIFAN LOKAL (A Literature Review) - Rusdiyana, Rusdiyana; Nurwahyunaniâ€¬, â€ªAtip; Marianti, Aditya (Badan Pengembang Konservasi UNNES, 2021)
Sustainable Development Goals (SDGs) implies a direct relationship between biodiversity and human well-being. The agricultural sector has a major contribution in supplying food needs and increasing the economy of a region.In addition, the agricultural sector is also known to contribute to soil degradation. The purpose of writing this literature review is to analyze the role of farmers in land conservation based on local wisdom and their contribution to the return of land functions. This research uses literature study method by analyzing several articles. The stages of the literature review method include; 1) Manuscript Selection. The articles analyzed were obtained using the Harzing's Publish or Perish application with restrictions from 2010 to 2021 by entering the keywords â€œthe role of farmersâ€, â€œland conservationâ€, and â€œlocal wisdomâ€. The search results found as many as 53 articles in Indonesian and English, then 26 articles were obtained that met the review standards for analysis, 2) Analysis of articles that meet the criteria using qualitative content analysis methods, namely thematic analysis that focuses on the relationship between content and context. The results of the literature review show that: 1). There are several concepts of local wisdom that have been successfully applied in Indonesia in order to maintain potential land, namely: Baduy farmers in Banten, farmers in Hutan Gurgur Village, Silaen sub-district, Toba Samosir district, farmers in Kemiren Banyuwangi, farmers in Solo and Farmers in the village of Malaris, Maratus Mountains, South Kalimantan. Traditional farmers in Indonesia to maintain the productivity of agricultural land and prevent land degradation, have carried out good soil management, including planting terrace strengthening plants that are tolerant to the local climate, and returningÂ fertilizing.